Microsurgical varicocelectomy effect on sperm telomere length, DNA fragmentation and seminal parameters. (1st January 2022) - Lara-Cerrillo, Sandra; Gual-Frau, Josep; Benet, Jordi; Abad, Carlos; Prats, Juan; Amengual, María José; Ribas-Maynou, Jordi; García-Peiró, Agustín
Abstract: Varicocele is one of the main causes of male infertility and microsurgical varicocelectomy (MV) seems to be the best procedure for its repair and to reduce testicular oxidative stress (ROS). As ROS causes guanine modifications, we postulated that DNA damage could be more intense in telomeres due to their G-rich nature. We studied the effect of MV on sperm telomere length (TL), single- and double-strand DNA fragmentation (ssSDF and dsSDF) and seminal parameters. Sperm telomeres from 12 fertile donors and 20 varicocele patients before and nine months after MV were labelled using FITC-PNA qFISH (a new method to obtain absolute TL from relative fluorescence intensity using FITC-fluorescent spheres). Both ssSDF and dsSDF were analysed using the alkaline and neutral Comet assays, respectively. The results showed that varicocele and MV had no effect on TL. Seminal parameters, ssSDF and dsSDF of varicocele patients were altered. Although these parameters improved after MV, values did not reach those seen in fertile donors. A good estimation of absolute TL was developed based on FITC-fluorescent spheres. The results showed that TL is not affected by varicocele or surgery. However, MV is able to partially reduce altered seminal parameters, ssSDF and dsSDF values in varicocele patients.